THE SEVERAL FACES OF SCHMORL'S NODE: PICTORIAL ESSAY - Nogueira-Barbosa,Marcello Henrique (2015)
The aim of this review is to present the imaging features of Schmorl's node (SN) occurring in conjunction with several etiologies. The SN is a relatively common finding in diagnostic spinal imaging. This condition is usually asymptomatic and its etiology is not always clear. Any disorder that weakens the subchondral bone of the vertebral body may lead to endplate disruption and consequent intravertebral disc herniation. SN is a common finding among asymptomatic patients, but may possibly be accompanied by symptoms in cases of trauma, hemispherical spondylosclerosis, calcific discitis with intravertebral migration, inflammatory diseases and neoplasms. Even though SN is generally associated with benign diseases, its presence does not exclude the possibility of concomitant malignancy in the vertebral body. Radiologists and spine surgeons must be aware of uncommon conditions that might be associated with SNs, as well as related radiological findings, in order to avoid misdiagnosis.